Self-assembled cellulose nanofiber–carbon nanotube nanocomposite films with anisotropic conductivity. Issue 2 (15th December 2021) - Skogberg, Anne; Siljander, Sanna; Mäki, Antti-Juhana; Honkanen, Mari; Efimov, Alexander; Hannula, Markus; Lahtinen, Panu; Tuukkanen, Sampo; Björkqvist, Tomas; Kallio, Pasi
Abstract : c-CNFs were used as an aid to disperse CNTs, and additional c-CNFs guided the self-assembly between nanocomponents resulting in a nanocomposite film with anisotropic properties. Abstract : In this study, a nanocellulose-based material showing anisotopic conductivity is introduced. The material has up to 1000 times higher conductivity along the dry-line boundary direction than along the radial direction. In addition to the material itself, the method to produce the material is novel and is based on the alignment of cationic cellulose nanofibers (c-CNFs) along the dry-line boundary of an evaporating droplet composed of c-CNFs in two forms and conductive multi-walled carbon nanotubes (MWCNTs). On the one hand, c-CNFs are used as a dispersant of MWCNTs, and on the other hand they are used as an additional suspension element to create the desired anisotropy. When the suspended c-CNF is left out, and the nanocomposite film is manufactured using the high energy sonicated c-CNF/MWCNT dispersion only, conductive anisotropy is not present but evenly conducting nanocomposite films are obtained. Therefore, we suggest that suspending additional c-CNFs in the c-CNF/MWCNT dispersion results in nanocomposite films with anisotropic conductivity. This is a new way to obtain nanocomposite films with substantial anisotropic conductivity.